Compensation policy without proof the fault on adverse events in Thai healthcare during 2004-2016. - Tipwong, Rustanasit; Watanasub, Nisaporn; Punnarrunothai, Supasit; Leesmidt, Vinai (Journal of Community Development Research (Humanities and Social Sciences); Vol 10 No 4 (2560): October-December 2017, 2017)
Comprehensive knowledge about healthcare policy should be encouraged among Thai people. Especially, compensation policy without proving fault on adverse events is useful for Thais. Various documents related to the compensation policy that have been reviewed are able to develop this policy. This study used the method of documentary analysis from Thai healthcare compensation policy during 2004-2016. It presented preliminary compensation regulations from the past until now. This presented operational data, analysis and synthesis of regulations, discussions, problems and suggestions. Results of documentary analysis explained the process of compensation policy as follows: 1) Regulations of preliminary compensation funds, 2) Concept and objectives of allocated funds, 3) Definition of damage, 4) Scope and conditions of damage, 5) Types of damage payment rates, 6) Procedures of the rights to claim, 7) Process of considering and deciding on preliminary compensation, 8) Appeals process of claimants, 9) Number of claimants in each year, 10) Rates of accepted claimants in three periods, 11) Types of files to claim, 12) Budgets of preliminary compensation funds, 13) Rates of allocated and actually paid budgets, 14) Satisfaction to initial assistance mechanism, and 15) Number of medical lawsuits that were sued. All details above should benefit the development of the compensation policy appropriate to the Thai people.